A Willingness-to-Pay Associated Right Prefrontal Activation During a Single, Real Use of Lipsticks as Assessed Using Functional Near-Infrared Spectroscopy - Hirabayashi, Kazue; Tokuda, Tatsuya; Nishinuma, Tomomi; Kawabata Duncan, Keith; Tagai, Keiko; Dan, Ippeita (Frontiers in Neuroergonomics, 2021)
Understanding consumer preferences and behavior is a major goal of consumer-oriented companies. The application of neuroscience to this goal is a promising avenue for companies. Previously, we observed a positive correlation during actual cosmetic use between the right dorsolateral prefrontal cortex (dlPFC) activity, measured by functional near-infrared spectroscopy (fNIRS), and the associated willingness-to-pay (WTP) values. However, we were unable to find any consistent group differences in the right dlPFC between different powdery foundations. Thus, the main objective of this study was to replicate the previous study and in addition, we aimed to refine the method of the previous study to increase the chance that a difference in valuation between different products can be detected. Twenty-five frequent lipstick using females were asked to apply six different lipsticks to their lips and to record how much they were willing to pay. To maximize the variation of the subjective experience of the products and the associated brain activity, the most preferred color lipstick and a less preferred color lipstick were chosen for each participant, and each color of lipstick had three different textures (Lo, Mid, and Hi). The time series was analyzed with the general linear model (GLM) and the correlation between the right dlPFC beta scores for the lipsticks and their respective WTP values conducted for each participant. This revealed a significant positive correlation and replicated our previous study. Surprisingly, the lipstick color and the texture manipulations did not result in any consistent differences in WTP and similarly no consistent group differences in brain activations. This study replicates our previous study extending it to a different type of cosmetic. The right dlPFC activity during the use of cosmetics may be a potential brain-based personalization or product selection process biomarker.